Pengaruh Pertumbuhan Penjualan, Leverage Dan Ukuran Perusahaan Terhadap Profitabilitas: Studi Pada Perusahaan Sub Sektor Telekomunikasi yang Terdaftar pada BEI Periode 2016 - 2020 - Eva Ahmad; Rega Verdika (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
Profitability is one of the most important ratios for the company because profitability is a measure of the success of the company’s performance, which in achieving profitability bis closely related to sales, assets and capital. This research aims to determine the effect of sales growth, leverage and firm size on profitability in companies sub-sector of telecommunication listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used is purposive sampling. Populations of 20 and the samples was 9 companies for 5 years, then the observation data of this research is 45. The data used in this research are secondary data obtained through the Stock Exchange Gallery. Data analysis in this reseach used multiple linear regression analysis whit SPSS 25. Based on the result of sales partial growth and leverage have a significant effect on profitability, and firm size not has a effect on profitability